ENGINEERING PHYSICS FIRST-YEAR STUDENT ASSESSMENT: A CASE STUDY ON BASIC PHYSICS 2 LABORATORY REPORT WRITING - Pranata, Nicholas (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2025)
Engineering has played an important role in human activities through technological development and the Industrial Revolution. The significance of engineers conveys the need for professional graduates who comply with the world's demands. Thus, engineering education that fulfills certain standards is crucial. Aside from the technical aspect, non-technical abilities such as writing are similarly fundamental, especially for first-year students. Thus, this research is conducted to analyze the report writing of the first-year engineering students particularly for the engineering physics department of UMN in Basic Physics 2 Laboratory course. The qualitative method is used for a case study on four individuals, and their reports on 10 different modules are compared with the rubric assessment given by the lecturer. Results show sufficient understanding and performance of the topic and writing aspect though additional notes for further elaboration in data completion and critical analysis are needed to ensure improvisation as their self-efficacy and self-concept is considered low. Recommendations for students from the preparation to evaluation stages are given to build positive self-concept and self-efficacy.